ANALISIS PERBANDINGAN LUAS PANEN PADI DAN PRODUKTIVITAS PADI TERHADAP PERTUMBUHAN PRODUKSI PADI DI PULAU KALIMANTAN PERIODE 2021-2024 - SYAWALUDIN, MUHAMMAD; ALFIYANI, NUR (Ganec Swara, 2025)
The rice farming sector in every region of Kalimantan Island in Indonesia is one of the supporting sectors for GDP in Indonesia. However, its contribution is still far behind Java Island, which is the largest supplier of GDP in the rice farming sector in Indonesia. One of the factors that determines the high and low GDP in the agricultural sector, especially rice crops, is the growth rate of rice production. The purpose of this study was to analyze the comparison of the highest and lowest rice harvested area, rice productivity and rice production growth in each province in Kalimantan Island for the period 2021-2024 and to analyze the effect of rice harvested area and rice productivity on rice production growth in various provinces in Kalimantan Island for the period 2021-2024. The method used is a quantitative approach in analyzing secondary data from the Central Statistics Agency according to a time series model from 2021-2024. The results found showed that not all rice harvested areas had a significant effect on rice production growth in a region. Rice production growth will increase if the two variables simultaneously, namely the amount of rice harvested area and rice productivity, have a high interaction.